1984
DOI: 10.1002/ajim.4700050506
|View full text |Cite
|
Sign up to set email alerts
|

Further cases of lead poisoning from wine

Abstract: Lead intoxication has been reported to occur as a consequence of nonoccupational exposure, the source being mostly the leaching of lead from fluid containers in domestic use. Three such cases are described, for which the cause has been identified to be in the lining of the vat used to contain home-made wine. All cases are members of the same family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In one study it was found that lead poisoning was caused by wine passing through lead-containing outlet tubes of storage casks (9). There have also been cases of lead poisoning from homemade wine where storage and fermentation vats contained lead (10,11). The storage of port and alcohol products in lead crystal decanters is another source of lead contamination (12), as is chewing of the lead foil closures on the neck of wine bottles (13).…”
Section: Grand Rounds In Environmental Medicinementioning
confidence: 99%
“…In one study it was found that lead poisoning was caused by wine passing through lead-containing outlet tubes of storage casks (9). There have also been cases of lead poisoning from homemade wine where storage and fermentation vats contained lead (10,11). The storage of port and alcohol products in lead crystal decanters is another source of lead contamination (12), as is chewing of the lead foil closures on the neck of wine bottles (13).…”
Section: Grand Rounds In Environmental Medicinementioning
confidence: 99%